Dico : um modelo conceitual para apoiar o design e a avaliação de recursos de busca avançada para pesquisa exploratória - Duarte, Emanuel Felipe (2015)
The design of models and tools to support Exploratory Search acquires more importance as the amount of information on the Web grows, because the attention capacity of human being is limited and there is a need to filter this information. The use of advanced search features is a viable approach for query exploration during Exploratory Search. However, the usage of advanced search features remains relatively low since Web search engines became popular, partially because of design decisions that ignore the complex and flexible nature of search activities. This dissertation investigates the design and evaluation of advanced search features that makes sense to users, favoring Exploratory Search activities. As a contribution, this work introduces Dico: a conceptual model for advanced search features for Exploratory Search, presenting and evaluating a set of guidelines created to support designers and evaluators of Exploratory Search tools to design better advanced search features, promoting their usage. To demonstrate the application of Dico, it was used to instantiate a Web Exploratory Search tool called Dico 01. The demonstration described the process of inspecting the tool using Dico's guidelines, which allowed the identification of improvement opportunities later addressed with the design of new features. Dico was used and evaluated by 13 prospective designers in a practical activity. The results indicated that Dico's guidelines made sense and supported most participants when inspecting a search engine, suggesting the usefulness and practical applicability of the guidelines.